Do fato intelectual à atividade real: um estudo das concepções de prática docente de professoras e professores de filosofia no Ensino Médio - Carreiro, Gabriela da Nóbrega (2018)
This paper has like objective to understand how the teachers of philosophy at high school correlate their conceptions of the world with their teaching practices in the public schools of João Pessoa, Paraíba. The philosophy teaching not always had been in the Brazilian school curriculum. Their requirement or release was observed, in this research, in the regulations: Law 4.024 of 1961; Law 5.692 of 1971; Law 9.394 of 1996 and Law 11.684 of 2008. With these education regulations, we place the philosophy teaching in the high school and introduce how those documents are related with the hegemonic social project, which determines the philosophy sometimes as dispensable and dangers knowledge, sometimes as necessary and basic in the formation for the citizenship. In this way, we emphasize the reality of the philosophy teaching in the basic education in the voices of the teachers. For this, we dialogue with the analytical categories (history, education and conceptions of the world), based in the theories of Gramsci (2017), Saviani (2011; 2013c; 2015), Silveira (1991). The epistemological approach of that research was the historical and dialectical materialism introduced for Marx (2010) e Marx e Engels (2007). The method was dialectic and founded in Triviños (2015) and Gamboa (2012). With the semistructured interviews, we could observe the necessary information to reach the principal objective of this research. The analysis of those reports highlighted three regular empiric categories: identity, started formation and teaching practice. The analysis had, as interpretative foundation, the Dialectical Hermeneutics introduced for Stein (1987) and Minayo (2014), based in the dialogs of Gadamer (2012) e Habermas (1987). From that analytical categories, the conceptions of the teaching practices shows the historical understanding, which placed the teachers of philosophy as individuals who assume every day the function of consolidate, in the basic education, a space of philosophical knowledge.